2002
DOI: 10.1111/j.1559-1816.2002.tb01436.x
|View full text |Cite
|
Sign up to set email alerts
|

A Place to Heal: Environmental Sources of Satisfaction Among Hospital Patients1

Abstract: Telephone interviews with 380 discharged inpatients were conducted to identify environmental sources of satisfaction with the hospital, to determine the relative contribution of environmental satisfaction to overall satisfaction with the hospital experience, and to explore differences in satisfaction across 4 departments (medical, obstetrics, orthopedics, and surgical) and 6 hospitals. Analyses indicate that interior design, architecture, housekeeping, privacy, and the ambient environment were all perceived as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
167
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(173 citation statements)
references
References 18 publications
2
167
0
4
Order By: Relevance
“…In other words, the quality of the healthcare setting from the users perspective (Gifford, 2002), and the quality of the social and organizational relationships in general, including the relationship with the staff (Irurita, 1999), are crucial for patients' satisfaction with the hospital experience. Harris et al (2002) interviewed 380 discharged inpatients to identify environmental sources of satisfaction with the hospital, and, specifically, to determine the relative contribution of environmental satisfaction to overall satisfaction with the hospital experience. Environmental satisfaction, that is, satisfaction with interior design, architecture, housekeeping, privacy, and the ambient environment was perceived as a source of overall satisfaction, following nursing and clinical care.…”
Section: From Perceptions Of the Quality Of The Health Care Environmementioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the quality of the healthcare setting from the users perspective (Gifford, 2002), and the quality of the social and organizational relationships in general, including the relationship with the staff (Irurita, 1999), are crucial for patients' satisfaction with the hospital experience. Harris et al (2002) interviewed 380 discharged inpatients to identify environmental sources of satisfaction with the hospital, and, specifically, to determine the relative contribution of environmental satisfaction to overall satisfaction with the hospital experience. Environmental satisfaction, that is, satisfaction with interior design, architecture, housekeeping, privacy, and the ambient environment was perceived as a source of overall satisfaction, following nursing and clinical care.…”
Section: From Perceptions Of the Quality Of The Health Care Environmementioning
confidence: 99%
“…Physical environment is defined as ambient, architectural or interior design features that are purely stimulus objects (Dijkstra et al, 2006;Harris et al, 2002) and that characterize the healthcare settings. Swan et al (2003) found that patients recovering in appealing rooms rated their rooms significantly higher than did patients in typical rooms in the same hospital, and Leather et al (2003) found that a relocated (and redesigned) waiting area originated more positive environmental appraisals, and greater reported environmental satisfaction than the traditional waiting area before relocation.…”
Section: Introductionmentioning
confidence: 99%
“…Natural light in patient care areas reduced agitation in elderly patients, decreased length of stay, lessened the need for pain medication, and reduced depression. [27][28][29][30][31][32][33] Researchers 34 reported that the cost of an inefficient system for navigation in a major regional hospital was more than $220 000 per year or $448 per bed. Much of this cost involved 4500 hours of hospital staff other than information staff giving directions.…”
Section: Patients and Their Families Weigh In On Evidence-based Hospimentioning
confidence: 99%
“…Numbers of research under western culture found elders living in shared bedrooms were more likely to develop territorial behaviors to protect personal privacy 1) . Consequently, most facility design guidelines in developed countries suggested that environment design should save enough personal space for each resident 2) , and private bedrooms are widely recommended over shared bedrooms.…”
mentioning
confidence: 99%